Effects and bioaccumulation of gold nanoparticles in the gilthead seabream (Sparus aurata) – Single and combined exposures with gemfibrozil. (January 2019) - Barreto, A.; Luis, L.G.; Pinto, E.; Almeida, A.; Paíga, P.; Santos, L.H.M.L.M.; Delerue-Matos, C.; Trindade, T.; Soares, A.M.V.M.; Hylland, K.; Loureiro, S.; Oliveira, M.
Abstract: Gold nanoparticles (AuNPs) are found in a wide range of applications and therefore expected to present increasing levels in the environment. There is however limited knowledge concerning the potential toxicity of AuNPs as well as their combined effects with other pollutants. Hence, the present study aimed to investigate the effects of AuNPs alone and combined with the pharmaceutical gemfibrozil (GEM) on different biological responses (behaviour, neurotransmission, biotransformation and oxidative stress) in one of the most consumed fish in southern Europe, the seabream Sparus aurata . Fish were exposed for 96 h to waterborne 40 nm AuNPs with two coatings – citrate and polyvinylpyrrolidone (PVP), alone or combined with GEM. Antioxidant defences were induced in liver and gills upon both AuNPs exposure. Decreased swimming performance (1600 μg.L −1 ) and oxidative damage in gills (4 and 80 μg.L −1 ) were observed following exposure to polyvinylpyrrolidone coated gold nanoparticles (PVP-AuNPs). Generally, accumulation of gold in fish tissues and deleterious effects in S. aurata were higher for PVP-AuNPs than for cAuNPs exposures. Although AuNPs and GEM combined effects in gills were generally low, in liver, they were higher than the predicted. The accumulation and effects of AuNPs showed to be dependent on the size, coating, surface charge and aggregation/agglomeration state of nanoparticles. Additionally, it was tissue' specific and dependent on the presence of other contaminants. Although, gold intake by humans is expected to not exceed the estimated tolerable daily intake, it is highly recommended to keep it on track due to the increasing use of AuNPs. Highlights: Antioxidant defences of Sparus aurata were induced after the gold nanoparticles (AuNPs) exposure. Polyvinylpyrrolidone coated AuNPs (PVP-AuNPs) induced more effects in the fish than citrate coated AuNPs (cAuNPs). Decreased swimming performance and oxidative damage were detected after PVP-AuNPs exposure. Gold accumulation and AuNPs toxicity were altered when fish were simultaneously exposed to AuNPs and gemfibrozil.